THE EFFECT OF GREEN MARKETING AND BRAND IMAGE ON THE PURCHASE INTEREST OF AVOSKIN PRODUCTS - Aldo Aldiansyah; Lis Tatin Hernidatiatin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The research of green marketing and brand image with purchase interest of Avoskin products. This research uses quantitative methodology with PLS-SEM analysis. Participants in this research are consumers acquainted with Avoskin products. The pool of participants was acquired using purposive sampling, selecting respondents using established standards, totaling 120 participants. Data were gathered with a Likert scale questionnaire. Research results demonstrate that green marketing positively and significantly purchase interest chances of purchasing Avoskin goods. The brand image has been demonstrated to exert a favorable and substantial influence on consumer purchasing interest. Additional data shows green marketing has the most substantial effect on increasing customer purchasing interest. These results underscore the need of adopting sustainable marketing tactics and enhancing brand image to maximize customer purchasing interest in Avoskin goods.